Exosomes as Efficient Nanocarriers in Osteosarcoma: Biological Functions and Potential Clinical Applications - Yang, Lingkai; Huang, Xin; Guo, Haoyu; Wang, Lutong; Yang, Wenbo; Wu, Wei; Jing, Doudou; Shao, Zengwu (Frontiers in Cell and Developmental Biology, 2021)
Osteosarcoma is the most common bone tumor affecting both adolescents and children. Although localized osteosarcoma has an overall survival of >70% in the clinic, metastatic, refractory, and recurrent osteosarcoma have poorer survival rates. Exosomes are extracellular vesicles released by cells and originally thought to be a way for cells to discard unwanted products. Currently, exosomes have been reported to be involved in intercellular cross-talk and induce changes in cellular behavior by transferring cargoes (proteins, DNA, RNA, and lipids) between cells. Exosomes regulate osteosarcoma progression, and processes such as tumorigenesis, proliferation, metastasis, angiogenesis, immune evasion, and drug resistance. Increasing evidences shows that exosomes have significant potential in promoting osteosarcoma progression and development. In this review, we describe the current research status of exosomes in osteosarcoma, focusing on the biological functions of osteosarcoma exosomes as well as their application in osteosarcoma as diagnostic biomarkers and therapeutic targets.